ANALISIS KOMPARATIF FAKTOR PENYEBAB PENGANGGURAN PADA LULUSAN SD, SMP, SMA, DAN SARJANA USIA PRODUKTIF MUDA - Artika Ananda Dewi; Ana Putri Anggreani; Ayyesha Letizia Elsyarif; Andini Uswatun Khasanah; Nina Farliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Unemployment remains a significant labor issue in Indonesia, particularly among young people of productive age with diverse educational backgrounds. This study aims to analyze the differences in the causes of unemployment based on educational level, namely elementary school, junior high school, high school/vocational school, and university graduates. The study uses a comparative qualitative approach with a case study design. Data were obtained through semi-structured interviews with respondents aged 16-30 years selected using purposive sampling techniques, then analyzed using Miles and Huberman's interactive model. The results showed that the causes of unemployment differed at each level of education. Among elementary and junior high school graduates, unemployment was influenced by low levels of education and limited skills. For high school/vocational school graduates, the main obstacles are related to high job competition and minimal work experience. Meanwhile, for university graduates, unemployment is more influenced by high job competition, work experience requirements, and skill mismatch with labor market needs. The results of this study show the importance of improving the quality of human resources through relevant job training and strengthening the link between education and the needs of the world of work.